KERJASAMA UNICEF-UNFPA DALAM MENCEGAH PERKAWINAN ANAK DI INDIA TAHUN 2016-2019 - Jiwami, Dian Justicia (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
Child marriage is a problem that can be found in all countries, especially developing countries. India is the country with the highest child marriage rate. The complexity and high level of child marriage is caused by economic pressures, cultural and social norms that are dominated by patriarchal ideology, and gender inequality, placing girls very vulnerable to become victims of child marriage. Through a global program carried out by UNICEF and UNFPA to end the practice of child marriage in India, it has had a positive impact with public awareness, especially girls and parents about reproductive and mental health, as well as the negative impacts caused by child marriage. Cooperation between UNICEF and UNFPA also encourages the government to make policies to reduce child marriage.